2014
DOI: 10.5901/mjss.2014.v5n9p23
|View full text |Cite
|
Sign up to set email alerts
|

Does Customer Satisfaction Lead to Customer Trust, Loyalty and Repurchase Intention of Local Store Brands? The Case of Gauteng Province of South Africa

Abstract: Notwithstanding the increasing researches on consumer behaviour

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Hypothesis seven results are not without empirical support. This study validated the significant role of satisfaction in triggering repurchase intent, which is in line with the existing stream of literature in this space (Abdul-Muhmin, 2010;Atulkar & Kesari, 2017;Chinomona & Dubihlela, 2014;Ebrahim et al, 2016;Ibzan et al, 2016;Liao et al, 2017;Pearson et al, 2012). As pointed out by Chopdar & Balakrishnan (2020) as well as Chung et al (2016), satisfaction is a strong determinant of whether shoppers will continue using a mobile shopping application.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Hypothesis seven results are not without empirical support. This study validated the significant role of satisfaction in triggering repurchase intent, which is in line with the existing stream of literature in this space (Abdul-Muhmin, 2010;Atulkar & Kesari, 2017;Chinomona & Dubihlela, 2014;Ebrahim et al, 2016;Ibzan et al, 2016;Liao et al, 2017;Pearson et al, 2012). As pointed out by Chopdar & Balakrishnan (2020) as well as Chung et al (2016), satisfaction is a strong determinant of whether shoppers will continue using a mobile shopping application.…”
Section: Discussionsupporting
confidence: 87%
“…Literature further reveals that there is a positive link between shoppers' satisfaction and repurchase intention (Abdul-Muhmin, 2010;Chinomona & Dubihlela, 2014;Ebrahim et al, 2016;Ibzan et al, 2016;Liao et al, 2017;Pearson et al, 2012;Singh, 2017). This is attributed to the fact that satisfied consumers tend to revisit and repurchase from stores where they know they have had a positive experience before, as their recollection of the experience serves as evidence that they are likely to experience a similar situation again (Chopdar & Balakrishnan, 2020;Srivastava & Sharma, 2013;Vijay et al, 2017).…”
Section: The Influence Of Digital Satisfaction On Repurchase Intentionmentioning
confidence: 99%
“…Maintaining relationships with customers needs to be applied in a company because a harmonious relationship in the long term will be profitable for the company and achieve customer satisfaction. Customer satisfaction, according to (Chinomona & Dubihlela, 2014;Tohara et al, 2020;Uma, 2015), is defined as the result of expectations for perceived quality, the extent to which the perceived service performance meets customer expectations or fails to meet previous expectations.…”
Section: Customer Relationship Management and Customer Satisfactionmentioning
confidence: 99%
“…A high level of trust in a brand will generate favorable attitudes [34]. Previous studies have shown that brand trust is one of the most important Antecedents of consumer loyalty and repurchase intention [35]. Studies have shown that once members feel trusted by the community, they are more inclined to show positive behaviors towards the community brand and other community members [36].…”
Section: Online Brand Community Trust and Customer Loyaltymentioning
confidence: 99%